2018
DOI: 10.1111/iep.12300
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1‐induced cell motility but not cell proliferation is mediated through Cten in colorectal cancer

Abstract: Summary Cten (C‐terminal tensin‐like) is a member of the tensin protein family found in complex with integrins at focal adhesions. It promotes epithelial‐mesenchymal transition (EMT) and cell motility. The precise mechanisms regulating Cten are unknown, although we and others have shown that Cten could be under the regulation of several cytokines and growth factors. Since transforming growth factor beta 1 (TGF‐β1) regulates integrin function and promotes EMT/cell motility, we were prompted to investigate wheth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…We have found that ROCK1 is a target of Cten 18 and it would seem that Src is able to induce ROCK1 expression. Immunostaining for ROCK1 was performed and cytoplasmic ROCK1 expression was observed (Fig.…”
Section: Comparison Of Cten Expression and Src Expressionmentioning
confidence: 84%
See 2 more Smart Citations
“…We have found that ROCK1 is a target of Cten 18 and it would seem that Src is able to induce ROCK1 expression. Immunostaining for ROCK1 was performed and cytoplasmic ROCK1 expression was observed (Fig.…”
Section: Comparison Of Cten Expression and Src Expressionmentioning
confidence: 84%
“…Changes in protein level of Src, ROCK1 and Snail were determined by Western blot and quantified by densitometry (Figure S1). We have previously shown that Snail is a target of Cten and, more recently, we have shown that ROCK1 is a target of Cten . These constructs were used to validate the effect of modulation of Cten expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of TNS4, the effects of TGF-ß stimulation on inducing motility and invasion were abrogated, but TGF-ß-induced proliferation was not affected [12] . Furthermore, TNS4mediated Src stabilization was found to be the responsible for EMT induction in CRC cell lines [13] Nude mice receiving a splenic injection of TNS4 overexpressing HCT116 cells have produced larger splenic tumours and hepatic metastatic nodules compared to the control group [5] .…”
Section: Introductionmentioning
confidence: 97%
“…The most explored of these is TNS4 and recently it has been shown that TNS4 is involved in the transduction of extra-celluar signals for a wide variety of growth factors. These data place TNS4 at the heart of a nexus of signalling pathways, the paradigm of which would be EGFR/KRAS/MAPK signalling (Albasri et al, 2011a;Al-Ghamdi et al, 2013;Thorpe et al, 2015;Asiri et al, 2018bAsiri et al, , 2019. In this pathway, TNS4 has been shown to mediate its effect through the reduction of EGFR degradation (Hong et al, 2013) by interacting with the phosphotyrosine residues of EGFR through its SH2 domain (Figure 4).…”
Section: Homology and Evolutionary Biology Of Tensinsmentioning
confidence: 96%